Application of hot-melt extrusion technology for designing an elementary osmotic pump system combined with solid dispersion for a novel poorly water-soluble antidepressant. (16th November 2016) - Zhang, Xuemei; Wang, Meng; Li, Pei; Wang, Aiping; Liang, Rongcai; Gai, Yunyun; Liu, Wanhui; Li, Youxin; Sun, Kaoxiang
Abstract: TP1 is a novel antidepressant with poor solubility. To reduce fluctuations in blood concentration and increase oral bioavailability, a controlled-release system was developed by combining a solid dispersion (SD) and an elementary osmotic pump (EOP). The study compared different methods of preparing SDs. Hot-melt extrusion (HME) exhibited clear advantages over the traditional melting technique. An in vitro release study demonstrated that HME-EOP tablets released TP1 in a zero-order manner over 12 h and the drug release was in dependent of the release medium and agitation speed, whereas release from molten-EOP tablets lasted only 8 h. In contrast to immediate-release tablets, the HME-EOP tablets exhibited less fluctuation in blood concentration and higher bioavailability in vivo . In summary, the osmotic pump system combined with an HME-based SD of TP1 presented controlled release in vitro, high bioavailability in vivo and a good in vivo – in vitro correlation.